Dietary intake and adherence to the Mediterranean diet in semi-professional female soccer players: a cross-sectional study - Modena, Alessandro; Casiraghi, Maria Cristina; Erba, Daniela (Frontiers in Nutrition, 2024)
Background. Adequate energy and nutrient intakes in athletes contribute to optimal performance and recovery, decrease the risk of injury, and help preserve athletes' health. The Mediterranean diet (MD) is considered suitable for covering the nutritional needs of athletes, while contributing to improve eating habits. The aim of the present study was to investigate the energy and nutrient intakes of semiprofessional female soccer players and their adherence to the MD, during the competitive season.Methods. A cross-sectional observational study was conducted on twenty-three female soccer players, who were invited to fill in a 3-day food diary twice, one month apart, to assess their energy and nutrient intakes and a validated questionnaire (MEDI-LITE) to evaluate their adherence to MD. Exercise energy expenditure during three training and match-play days was monitored by GPS.Results. On average, the participants consumed 1981 kcal/day, with 44% of their energy deriving from carbohydrates, 21% from protein, and 34% from fat; the mean MD adherence score was 10.1 ± 1.8, corresponding to a good MD adherence. A substantial percentage of athletes were at risk of insufficient nutrient intakes for vitamin D (100%), iodine (87%), potassium (87%), vitamin E (39%), iron and zinc (17% and 30%, respectively).Conclusion. The evaluation of the dietary intake in female soccer players showed energy deficiency in relation to training level, mainly due to the insufficient intake of carbohydrates, and micronutrient deficiencies. The technical staff should promote adequate consumption of starchy foods in female athletes and emphasize the importance of a proper distribution of energy intake among different eating occasions, including snacks. Periodic monitoring of the nutritional status of micronutrients (vitamin D and some minerals) could help reduce deficiency risk. Over all, nutrition education to improve eating habits of athletes seems worthy of attention, in order to preserve athletes' health and performance.